The hidden curriculum (2004)
This article shows the way hidden curriculum goes farther than just being the conscious and unconscious setting within the formal instruction context. It also shapes students personality and assigns to each individual the role they are supposed to play in society. In this process, interaction with the teacher is crucial since he/she is the one who directly moulds and cultivates the singularity of students according to the specific demands of the social class to which they belong. This phenomenon is well described in research conducted by Jane Anyon (1980) which is referred to in this paper as an example of the influence of the hidden curriculum on school life. Key words: Hidden Curriculum, Unconscious Setting, Teacher’s Role, Singularity, Society Este artículo muestra cómo el currículo oculto va más allá de ser simplemente el escenario consciente e inconsciente en el que se desarrolla la instrucción formal. El currículo oculto define la personalidad del estudiante y asigna a cada uno el papel que se supone debe ocupar en la sociedad. En este proceso, la interacción directa con el docente es decisiva ya que es éste quien directamente moldea y cultiva la singularidad de los estudiantes según las exigencias específicas de la clase social a la que pertenecen. Dicho fenómeno se describe muy bien en la investigación adelantada por Jane Anyon (1980), a la cual se hace referencia en este escrito, como ejemplo de la influencia del currículo oculto en la vida escolar. Palabras claves: Currículo Oculto, Escenario Inconsciente, Rol del Docente, Singularidad, Sociedad